EVALUATE THE PYHSICAL AND PHYSIOLOGICAL CHARACTERISTICS OF TURKISH NATIONAL BEACH SOCCER PLAYERS - Bozdogan, Tuba Kizilet (Acta Scientiae et Intellectus, 2024)
Beach soccer plays amauter and professional level in the world. And the game has more question about player’s performance profile in match. The purpose of this study was to evaluate the pyhsical and physiological charecteristics and effect of match load on charecteristics before match and after 1. period, 2. period and 3. period of beach soccer players. 12 beach soccer players who play in Turkish National Team (age; 28,33±3,70, height;179,4±8,26 cm, weight; 79,25±9,13 kg.) were particapated in this study. All meausurements were done during Turkish Beach Soccer Final Competition. Before and after match all players performed countermovement jump (CMJ) and squat jump (SJ) tests. Lactate consumption tests (Scout lactate analyzer, Germany) were done before match, after 1. 2. period and end of the match. During the match, the physical load was evaluated by means of heart rate was continuously recorded every 5s (polar team system, Polar eloctro, Finland). Before and after match there were no significant differences in CMJ and SJ. Statistically significant differences were found in heart rate and lactate levels during all periods of the game (p<0,05). One of in the match intensities research showed differences for HR categories and their interaction with match periods and LA values. With respect to pre-match condition (36.6 ± 5.3cm), higher CMJ performances were found at the end of the match periods (first=39.5±6.5cm; second=40.9±6.4cm; third=39.2±6.0cm). The present findings indicate that beach soccer is an intermittent sport activity that places a high load on players, with the anaerobic metabolism providing an important energy source during games (Scarfone, 2009). In another research showed that about CMJ and SJ with arms variables are 47.8 and 48.7 cm (Casajus, 2001) It is important that beach soccer which have difficult problem because of ground is more different than field of soccer. So physical and physiological load should evaluate and arrange apporiate training program.